Analisis Hukum Terhadap Perluasan Hak Monopoli Kepada Badan Usaha Milik Negara Oleh Presiden: Kajian Berdasarkan Perspektif Filsafat Hukum - Rasji; Erick Darmansyah (CV Rewang Rencang, 2024)
This study aims to analyze the expansion of monopoly rights granted by the President to State-Owned Enterprises under Law No. 1 of 2025 from the perspective of legal philosophy. The research method used is normative-philosophical with conceptual, historical, and juridical approaches through literature and regulatory analysis. The monopoly rights provision explicitly expands presidential authority to appoint State-Owned Enterprises’ as sole operators in vital sectors. While constitutionally grounded in Article 33 of the 1945 Constitution, such expansion raises concerns regarding distributive justice and legal certainty. Law No. 1/2025 lacks clarity on the required regulatory form, opening room for ambiguous interpretation and potential market inequality. From both positive law and progressive legal theory perspectives, unchecked monopolies may harm healthy market competition. Analysis through Aristotle’s justice theory, utilitarianism, progressive law, and law and economics approaches reveals the need for limitations based on justice, transparency, and public service efficiency. In conclusion, the expansion of monopoly rights must be regulated within a clear and accountable legal framework to protect public interest and avoid harming other business actors.